PIAK : a personalized internet access for kids - Abrar Noor Akramin, Kamarudin; Bali, Ranaivo-Malançon; Nadianatra, Musa (2017)
Children are Internet users and as such they need to be protected from all inappropriate information available on the Internet. This paper is describing the components of a Personalized Internet Access system for Kids called PIAK. This kind of systems will allow children to browse the Web in a secure environment. The personalized features are individual welcoming message, recommended webpages, a Web search guided by preferred categories, and targeted educative mediums. A preliminary usability assessment of the system is reported in this paper indicating that all implemented personalized features are working properly.